2021
DOI: 10.1108/bij-12-2020-0628
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction and value-in-use perceived by university students from the influence of the built environment, price fairness and teaching care

Abstract: PurposeThis research goal was to analyze factors that may influence value-in-use and satisfaction perceived by university students, from the built environment, price fairness and teaching care.Design/methodology/approachFor this purpose, a survey was conducted with 900 students from a university in southern Brazil.FindingsThe main results proved that the antecedents considered in the study have a significant and positive influence on the value-in-use and satisfaction of university students. Furthermore, the bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 61 publications
0
3
1
Order By: Relevance
“…Unexpectedly, this study reported that SAT does not significantly influence VIU. This result contradicts the previous argument of Da Silva et al (2022). However, this finding does not necessarily mean that SAT is not crucial.…”
Section: Discussioncontrasting
confidence: 90%
See 3 more Smart Citations
“…Unexpectedly, this study reported that SAT does not significantly influence VIU. This result contradicts the previous argument of Da Silva et al (2022). However, this finding does not necessarily mean that SAT is not crucial.…”
Section: Discussioncontrasting
confidence: 90%
“…Da Silva et al (2022) demonstrated a close relationship between SAT and VIU as after receiving services from universities, students assess the services and gain their perception of the outcomes from these services. VIU was used in different contexts, including sustainable tourism (Font et al, 2021), B2B market (Prohl and Kleinaltenkamp, 2020), university services (Da Silva et al, 2022) and residential buildings (Da Silva et al, 2020). However, the interpretation of the influence of SAT on VIU in m-banking has not yet been considered.…”
Section: Fairness Perception and Satisfaction Value-in-use And Positi...mentioning
confidence: 98%
See 2 more Smart Citations
“…Студентські послуги, що надаються різними університетськими підрозділами, викликають багато критики з боку студентів, які вважають їх важкодоступними та складними для сприйняття (Benetti Corrêa da Silva et al, 2021). Одним із рішень, які були запропоновані закладами вищої освіти та знайшли відображення в науковій літературі, є створення «центру студентських послуг» (De Silva & Garnaut 2011) або «єдиного вікна» (Morgan, 2012), що надає змогу надавати послуги в одному місці, заощаджуючи час студентів і даючи їм змогу краще в них орієнтуватися.…”
Section: неакадемічний студентський досвід: послуги для студентівunclassified